2006
DOI: 10.1097/01.sla.0000234892.79056.63
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Lobectomy Is a Safe and Versatile Procedure

Abstract: Thoracoscopic lobectomy is applicable to a spectrum of malignant and benign pulmonary disease and is associated with a low perioperative morbidity and mortality rate. Survival rates are comparable to those for lobectomy with thoracotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
230
2
16

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 376 publications
(264 citation statements)
references
References 26 publications
12
230
2
16
Order By: Relevance
“…Because technical difficulties are expected in complex cases, thoracotomy should be considered a prophylactic conversion rather than a failure of an intended minimally invasive approach in some patients. We find it hard to compare our conversion rate with published VATS series since most series have focused on early-stage lung cancer, excluded pneumonectomies and examined a more homogenous group of patients than this series (4,18). A preliminary analysis suggested that if only patients undergoing lobectomy or segmentectomy for early-stage lung cancer were analyzed, our conversions to thoracotomy would be solely due to 2 cases of vascular accidents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because technical difficulties are expected in complex cases, thoracotomy should be considered a prophylactic conversion rather than a failure of an intended minimally invasive approach in some patients. We find it hard to compare our conversion rate with published VATS series since most series have focused on early-stage lung cancer, excluded pneumonectomies and examined a more homogenous group of patients than this series (4,18). A preliminary analysis suggested that if only patients undergoing lobectomy or segmentectomy for early-stage lung cancer were analyzed, our conversions to thoracotomy would be solely due to 2 cases of vascular accidents.…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1990s, VATS operations were done through 3-4 surgical ports but gradually surgeons began to use only 2 ports for many surgeries: one for the camera and one as a working incision for insertion of all other endoscopic tools (4,(6)(7)(8). In 2004, the uniportal or single-port approach was introduced, initially for wedge pulmonary resection (9) and subsequently in 2010 for lobectomy (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In recent years, VATS lobectomy with a single utility port has been reported as a safe and reliable procedure with lesser invasion in several thoracic conditions, including lung cancer in selected patients. 17,23 However, reports of VATS lobectomy with a single utility port used in elderly patients are extremely rare. In this study, we retrospectively reviewed the surgical outcomes in elder patients who underwent VATS lobectomy with a single utility port in our institution.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In recent years, the use of VATS with a single utility port has become prevalent, requiring fewer incisions and providing quicker recovery times. 17 In this study, we retrospectively compared the surgical outcomes in elderly lung cancer patients who underwent VATS lobectomy with a single utility port and lobectomy by thoracotomy to elucidate the feasibility of the former in the treatment of lung cancer.…”
Section: Introductionmentioning
confidence: 99%